2021
DOI: 10.3390/en14113343
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Coverage of the Trust–Acceptability Model: The Negative Effect of Trust in Government on Nuclear Power Acceptance in South Korea under a Nuclear Phase-Out Policy

Abstract: This article extends the coverage of the trust–acceptability model to a new situation of nuclear phase-out by investigating the effect of trust on the public acceptance of nuclear power, with South Korea as the research setting. Through the structural equation modeling of a nationwide survey dataset from South Korea, we examined the effects of the public’s trust in the various actors related to nuclear power on their perceptions of the benefits and risks of nuclear power and their acceptance of nuclear power. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…In this context, research has shown that public acceptability of energy developments does not only relate to people's opinions of energy projects and forms of energy production themselves but also on what people think of those who regulate such endeavours [10]. In particular, literature on risk perception suggests that the degree of trust people have in the institutions responsible for managing hazard-prone activities, including energy production, relates to whether the public considers such activities acceptable or not (e.g., [10][11][12][13][14][15][16][17][18]). However, as most of the evidence stems from correlational studies, the direction of this relationship is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, research has shown that public acceptability of energy developments does not only relate to people's opinions of energy projects and forms of energy production themselves but also on what people think of those who regulate such endeavours [10]. In particular, literature on risk perception suggests that the degree of trust people have in the institutions responsible for managing hazard-prone activities, including energy production, relates to whether the public considers such activities acceptable or not (e.g., [10][11][12][13][14][15][16][17][18]). However, as most of the evidence stems from correlational studies, the direction of this relationship is unclear.…”
Section: Introductionmentioning
confidence: 99%